Pain, cannabis use, and physical and mental health indicators among veterans and nonveterans: results from the National Epidemiologic Survey on Alcohol and Related Conditions-III. Issue 2 (26th February 2022) - Enkema, Matthew C.; Hasin, Deborah S.; Browne, Kendall C.; Stohl, Malki; Shmulewitz, Dvora; Fink, David S.; Olfson, Mark; Martins, Silvia S.; Bohnert, Kipling M.; Sherman, Scott E.; Cerda, Magdalena; Wall, Melanie; et al.
Abstract : Supplemental Digital Content is Available in the Text. Pain is related to cannabis use, and the prevalence of cannabis use disorder is greater among veterans who reside in states with medical cannabis laws and report recent pain. Abstract: Chronic pain is associated with mental and physical health difficulties and is prevalent among veterans. Cannabis has been put forth as a treatment for chronic pain, and changes in laws, attitudes, and use patterns have occurred over the past 2 decades. Differences in prevalence of nonmedical cannabis use and cannabis use disorder (CUD) were examined across 2 groups: veterans or nonveterans and those reporting or not reporting recent pain. Data from the National Epidemiologic Survey on Alcohol and Related Conditions-III (2012-2013; n = 36, 309) were analyzed using logistic regression. Prevalence differences (PDs) for 3 cannabis outcomes (1) past-year nonmedical cannabis use, (2) frequent (≥3 times a week) nonmedical use, and (3) DSM-5 CUD were estimated for those reporting recent moderate to severe pain (veterans or nonveterans) and veterans reporting or not reporting recent pain. Difference in differences was calculated to investigate PDs on outcomes associated with residence in a state with medical cannabis laws (MCLs). Associations between physical and mental health and cannabis variables were tested. The results indicated that the prevalence of recent pain was greater among veterans (PD = 7.25%, 95% confidence interval (CI) [4.90-9.60]). Among veterans, the prevalence of frequent cannabis use was greater among those with pain (PD = 1.92%, 98% CI [0.21-3.63]), and among veterans residing in a state with MCLs, the prevalence of CUD was greater among those reporting recent pain (PD = 3.88%, 98% CI [0.36-7.39]). Findings failed to support the hypothesis that cannabis use improves mental or physical health for veterans with pain. Providers treating veterans with pain in MCL states should monitor such patients closely for CUD.